Life Is Short : An Appropriately Brief Guide to Making It More Meaningful - Rickles, Dean (Book collections on Project MUSE., 2022)
"Why life's shortness-more than anything else-is what makes it meaningfulDeath might seem to render pointless all our attempts to create a meaningful life. Doesn't meaning require transcending death through an afterlife or in some other way? On the contrary, Dean Rickles argues, life without death would be like playing tennis without a net. Only constraints-and death is the ultimate constraint-make our actions meaningful. In Life Is Short, Rickles explains why the finiteness and shortness of life is the essence of its meaning-and how this insight is the key to making the most of the time we do have.Life Is Short explores how death limits our options and forces us to make choices that forge a life and give the world meaning. But people often live in a state of indecision, in a misguided attempt to keep their options open. This provisional way of living-of always looking elsewhere, to the future, to other people, to other ways of being, and never committing to what one has, or else putting in the time and energy to achieve what one wants-is a big mistake, and Life Is Short tells readers how to avoid this trap.By reminding us how extraordinary it is not that we have so little time but that we have any at all, Life Is Short challenges us to rethink what makes life meaningful and how to make the most of it"--